Perfekcjonizm i stres a dobrostan psychiczny studentów uczelni wyższych. Testowanie modelu mediacyjnego - Słodkowska, Joanna; Bokszczanin, Anna (Acta Universitatis Lodziensis. Folia Psychologica, 2012)
The purpose of this study was to evaluate the link between perfectionism treated as a personality’s trait, academic stress and college students’ psychological well-being. It was expected that the greater intensity of perfectionism achieved, the lower level of psychological well-being and the higher level of stress experienced. It was also assumed that the level of experienced stress would be a mediator of the relationship between perfectionism and psychological well-being. Alternative model with the well-being as a mediator of the relation between perfectionism and stress was also verified. Results of the study conducted on a sample of 298 students supported our assumptions. Higher level of perfectionism was associated with both higher stress level and lower sense of psychological well-being. Paths analyses provided evidence that relationship between perfectionism and psychological well-being can be explained by the high level of experienced stress (partial mediation). The analyses of well-being as a mediator in the relation between perfectionism and stress proved to be statistically significant and well suited to the sample (complete mediation). Results of this study are interpreted according to the Hobfoll’s Conservation of Resources Theory and Multiaxial Model of Coping (1998, 2006).